2020
DOI: 10.1186/s12889-020-08763-w
|View full text |Cite
|
Sign up to set email alerts
|

Early exposure to social disadvantages and later life body mass index beyond genetic predisposition in three generations of Finnish birth cohorts

Abstract: Background: The study aimed to explore the association between early life and life-course exposure to social disadvantage and later life body mass index (BMI) accounting for genetic predisposition and maternal BMI. Methods: We studied participants of Helsinki Birth Cohort Study born in 1934-1944 (HBCS1934-1944, n = 1277) and Northern Finland Birth Cohorts born in 1966 and 1986 (NFBC1966, n = 5807, NFBC1986, n = 6717). Factor analysis produced scores of social disadvantage based on social and economic elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…25 It is important to note, however, that individual’s psychological well-being partly depend on the social environment we live in. 26 We observed a positive association between ‘ Factor1-BMI ’ and birth weight, consistent with observational studies. 27 28 Tyrell et al demonstrated a positive causal genetic association between maternal BMI and birth weight.…”
Section: Discussionsupporting
confidence: 90%
“…25 It is important to note, however, that individual’s psychological well-being partly depend on the social environment we live in. 26 We observed a positive association between ‘ Factor1-BMI ’ and birth weight, consistent with observational studies. 27 28 Tyrell et al demonstrated a positive causal genetic association between maternal BMI and birth weight.…”
Section: Discussionsupporting
confidence: 90%
“…However, using a stratified sampling approach and over-sampling in the ends of the distribution ensured that offspring with a full range of mppBMI and birth weight were included in our study. Second, while the PRS explained only a modest percent of the variation for BMI, this is similar to other studies and expected with the current methodology used (15, 35). Third, both mppBMI and GWG were reported by mothers in interviews conducted by nurses while hospitalized after delivery.…”
Section: Discussionsupporting
confidence: 89%
“…Parental ages and socioeconomic status (SES) determined by parents’ occupation were not associated with offspring’s BMI at age 32 and their inclusion in the model didn’t change the regression coefficient for PRS. In a study spanning three generations in Finland, early-life social disadvantages related to later-life BMI, but this association weakened when accounting for PRS (35). Interestedly, in the youngest cohort included in the study, the association between early social disadvantage and later life BMI was attenuated after adjusting for PRS.…”
Section: Discussionmentioning
confidence: 99%
“…health outcomes. This triggering point of poor health outcomes could be shorter among women of lower socioeconomic status due to a high level of chronic exposure to obesity risk factors from the sensitive teenage period, and because women with lower socioeconomic status are more vulnerable to these risk factors than women in high socioeconomic groups [16][17][18]. Among upper-level employees, the association between maternal age and maternal obesity across all age groups was weaker than that of other socioeconomic groups.…”
Section: Discussionmentioning
confidence: 99%